Constantinople capital of Byzantium - Harris, Jonathan 1961- (Hambledon Continuum, 2007)
Publisher's description -- Synopsis: This book examines the intriguing interaction between the spiritual and the political whilst reconstructs the awe-inspiring city in its heyday of 1200. Description: In the early Middle Ages, the greatest city in Europe was not Paris, London or Berlin but Constantinople, capital of Byzantium. It was an article of faith that a saintly emperor, divinely appointed, had founded Constantinople and that the city was as holy as Rome or Jerusalem. The Byzantine emperors assiduously promoted the notion of a spiritual aura around the city. Thus, in 917, the emperor's regent wrote to the khan of the Bulgars warning him not to attack Constantinople. He did not threaten the khan with military force, but with the Virgin Mary who, as 'commander in chief of the city', would not take kindly to any assault. It was with legends and beliefs like this that the emperors bolstered their power and wealth, and the myth was central to the success of Constantinople and its empire for over a thousand years. Although this is hardly the first history of Byzantium to be published, Jonathan Harris differentiates himself by offering keen insight into the spiritual and mythic dimensions of Constantinople, key elements of the city's history that have been neglected until now. Constantinople: Capital of Byzantine is the first history of this great empire to properly examine the intriguing interaction between the spiritual and the political, the mythical and the actual. The result is an accessible and engaging account of a colorful and vital time in human history, and a long overdue look at an awe-inspiring city in its heyday.